Needs Analysis on the Problems of Islamic Economics Students in Learning ESP at State College of Islamic Studies (STAIN) Pekalongan - Jaya, Jaya; Subiyanto, Agus (PAROLE: Journal of Linguistics and Education, 2017)
This paper aims to discuss the needs analysis on the problems of Islamic Economics students in learning ESP at STAIN Pekalongan. This study involved 41 students and 3 teachers as the subjects. The data in this research were analyzed by using SPSS program. The data used in this paper were taken from questionnaires given to the students and interviews of some lecturers. The method applied to investigate students’ problems in learning ESP was quantitative method and qualitative design in order to get reliable and valid interpretation of data analysis. The result shows that ESP problems include vocabulary (42.0%), course contents (22.0%), and grammar (12.0%). The result from the questionnaires show that the first problems are related to limited vocabulary (40.0%), lacks of students’ language skills (24.4%), and boring classes (14.4%). Some students also believe that 7.8% of problems are related to teaching materials (course contents) that the lecturers used, which are not suitable with their needs, and finally, the incompatibility of the lecturers, including difficult materials (6.7%).